Numerical Simulation for Mechanical Behavior of Asphalt Pavement with Graded Aggregate Base. (21st March 2018) - He, Dongliang; Cheng, Yanhui
Abstract : The performance of asphalt pavement is determined by the combination of its material properties, road structure, and loading configurations. A DEM numerical simulation study was conducted to determine stress distribution and deformation behavior of asphalt pavement with graded aggregate base under standard traffic loading. Stress contour and displacement contour were presented via a self-made program. Compressive stress concentrated area located in both sides of wheel, while tensile stress concentrated area appeared in lower part of the asphalt layer. The traffic loading transferred downward by graded aggregate base and to both sides at the same time, and has a trend to expand gradually with increasing depth within graded aggregate base. Therefore, stress was well distributed in the subgrade soil layer with a great action scope, and the value decreased obviously because of the stress dispersion of graded aggregate base. Vertical displacement was the main displacement of the asphalt layer, and on the both sides of traffic loading, displacement was downward and inclined slightly to the central of loading. Vertical and horizontal deformations included in both graded aggregate base layers, and displacement extended to both sides gradually with increasing depth corresponding to stress-distribution trends. Vertical displacement was dominated in the subgrade soil layer which was relatively small.